Motivation and risk factors inclining juveniles for terrorism - Maltsev, Alexander A.; Oganesyan, Ovsep A. (Opción, 2019)
In this article, we will summarize most of the factors which lead to the involvement of juveniles in terrorist activities via comparative research methodology. In result, there are a certain amount of children who join terrorists‘ voluntary having a specific motivation for joining terrorist groups. This motivation mostly is a result of a process of radicalization and the influence of some trigger factors. As a conclusion, the vast majority of individuals who live in deprived social conditions do not end up as terrorists despite natural feelings of injustice.